Experimental study on the efficacy of ultrasound in in-situ detection of corrosion in palm oil refining equipment - Tai, Jan Lean; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani (Penerbit UTM Press, 2024)
Palm oil is an important agricultural product for many countries. Stainless steel refining equipment faces corrosion challenges due to the corrosive nature of palm oil, which gradually deteriorates the equipment over time. Ultrasonic testing (UT) can detect corrosion, usually performed during palm mill downtime due to temperature constrain. The study aims to optimize UT at temperatures up to 250°C. The experimental outcomes serve as a foundation for broadening the application of phased array corrosion mapping (PACM) into elevated temperatures. The results offer intricate insights into velocity fluctuations within specific materials, correlating with temperature elevation. In summary, the suite of UT methods demonstrates their aptitude for employment during palm oil refinery operations up to 250°C involving carbon steel as well as 304 and 316 stainless steels. It allows further UT application during the palm mill’s operation and achieves the study’s objective of allowing palm mill owners to detect and monitor corrosion growths without stopping production.